THE POLITICAL SYSTEM IN THE REPUBLIC OF SOUTH SUDAN: UNDERSTANDING CONCEPTUAL THEORY OF THE SUDAN PEOPLE LIBERATION MOVEMENT GOVERNANCE SINCE 2005 - (PhD), Dr. Acwanyo Adam Thabo (IJRDO - Journal of Social Science and Humanities Research, 2023)
This study sheds light on the lack of a clear strategy for building the Governance system in South Sudan. The study employ variety of methods used among which are descriptive, inductive, deductive, statistical interview and questionnaire for collection of data pertinent to the study. In addition to qualitative and quantitative techniques. The data collected were analyzed by using both qualitative and quantitative methods. Data were analyzed by using Statistical Package for Social Science (SPSS) version 21.The key Findings, The Parliamentary and Federal system is the most preferable by majority of the respondents as the best for country with high illiteracy and tribal tendency. Application of democratic system is needed in South Sudan, for avoiding problem of one-party governance system. Key element of the Conclusion: The current political system doesn’t in any way represent the ideal state for democratic system. The necessity to initially develop inclusive coalition of stakeholders to come up with comprehensive permanent constitution. The federalism must be implemented to avoid ethnic and regional disintegration.